84 Carcass Characteristics, Meat Color and Fatty Acid Profile of Feedlot Lambs Fed Novel Anthocyanin-rich Corn Cobs. (8th March 2022) - Quadros, Danilo G; Xu, Wenwei; Kerth, Chris; Tolleson, Douglas; Whitney, Travis R
Abstract: Hi-A™ is a unique type of corn developed by Texas A&M AgriLife that has high anthocyanin. A completely randomized design trial was used to evaluate the effects of three roughages, Hi-A™ corn cobs, low-A (regular) corn cobs and bermudagrass hay (BGH), in feedlot Rambouillet ewe lamb (n = 10/treatment) diets on carcass characteristics, meat color and fatty acids (FA) profile. Lambs were fed experimental diets (20% roughage and 80% concentrate) for 63-d. Then, lambs were harvested, and the carcasses evaluated. Boneless lamb loin chops, 2.5 cm thick, were fabricated and analyzed for color and FA. Data were analyzed by ANOVA for a completely randomized design with diet as fixed effects and animal as a random effect with an alpha of 0.05. Carcass weight, loin eye area (LEA), body wall thickness, fat thickness, leg score, marbling, skeletal maturity, lean maturity, and flank streaking did not differ among treatments (P > 0.05). Dressing percentage was greater (P < 0.05) in the lambs fed BGH compared to Hi-A™ diets; neither of which differed (P > 0.05) from lambs fed Low-A. Instrumental color characteristics L* (darkness to lightness), a* (redness), b* (yellowness) and chroma (total color) of fresh lamb loin chops measured under retail display did not vary (P > 0.05) among treatments. Hue Angle (discoloration) was greater (P < 0.05) in loin chops from lambs fed Hi-A™ than Low-A diets, while BGH did not differ (P > 0.05) from the other treatments. Retail display day influenced (P < 0.05) all the instrumental color characteristics, with the highest values of L*, a*, b*, and chroma on day 1 and Hue Angle on days 3 and 4. No differences (P > 0.05) were observed in the meat FA profile. No advantages of using Hi-A™ corn cobs in feedlot lamb diets were observed regarding carcass characteristics, meat color and FA profile.